Bovine Endocarditis Associated with Mycoplasma bovis. (August 2019) - Kanda, T.; Tanaka, S.; Suwanruengsri, M.; Sukmawinata, E.; Uemura, R.; Yamaguchi, R.; Sueyoshi, M.
Summary: Mycoplasma bovis is a microorganism associated with pneumonia, mastitis, arthritis and otitis media of cattle; however, there are no reports of this organism causing bovine endocarditis. Five adult cattle with endocarditis characterized by caseated lesions (diameter 5–12 cm) of the endocardial surface of the left atrium, but without lesions in heart valves or affecting the right side of the heart, were identified in slaughterhouses in Japan. M. bovis was successfully isolated from the lesions and M. bovis antigen was detected immunohistochemically within the lesions. The results suggest that the lesions may have been associated with M. bovis alone. To our knowledge, this is the first demonstration of bovine endocarditis associated with M. bovis .